SUPPLEMENTATION OF COFFEE HUSK FERMENTED WITH Pleurotus ostreatus: EFFECT ON PERFORMANCE AND BLOOD PROFILE OF GASTROINTESTINAL NEMATODES INFECTED GOAT - Badarina, I.; Putranto, H. D.; Sulistyowati, E. (Diponegoro University, 2015)
The aim of this study was to investigate the potency of coffee husk fermented with P.ostreatus as a natural anthelmintic supplement by measuring the performance and blood profile of goat suffered gastrointestinal nematodes infection. Eighteen local male goats of Kacang goat with body weight of 9.23 ± 1.71 kg and aged at ± 10 months were arranged into three treatments in completely randomized design. The treatments were T0 (group without chemical anthelmintic treatment and no supplementation of fermented coffee husk), T1 (without chemical anthelmintic treatment, but supplied with fermented coffee husk) and T2 (group with chemical anthelmintic and no supplementation of fermented coffee husk). All goats were offered a basal diet in the ratio of 60% natural grasses along with 40% concentrate. Fermented coffee husk was added in the diet as much as 6% from the dry matter need. The result showed that there were no significant effect to dry matter intake, daily weight gain, PCV value and eosinophil counts (P>0.05). The supplementation of fermented coffee husk (T1) enhanced Hb and red blood cell (RBC) value (P